2011
DOI: 10.1016/j.nut.2010.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength and its dialysis determinants in hemodialysis patients

Abstract: Patients using HD presented a high prevalence of MF loss as assessed by HGS, and it was not influenced by dialysis variables. HGS may be used as a reliable nutritional marker in HD, measured before or after HD sessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0
27

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 30 publications
5
52
0
27
Order By: Relevance
“…Confirming our findings, in the study by Leal et al, HGS was negatively correlated with body fat ratio and it was not associated with BMI (22). This issue may be explained by the fact that BMI is not a reliable indicator of body composition, in other words it cannot differentiate muscle mass from hypervolemia or fat mass (23).…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nesupporting
confidence: 85%
“…Confirming our findings, in the study by Leal et al, HGS was negatively correlated with body fat ratio and it was not associated with BMI (22). This issue may be explained by the fact that BMI is not a reliable indicator of body composition, in other words it cannot differentiate muscle mass from hypervolemia or fat mass (23).…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nesupporting
confidence: 85%
“…Leal et al 27 , ao avaliar 43 pacientes submetidos a HD, encontrou que a FPM em homens foi significativamente maior do que em mulheres, não havendo diferença estatística em fazer o teste antes ou depois da sessão de HD. Concluiu também, diferentemente do presente estudo, que apesar da alta prevalência de diminuição da FPM, este achado não teve relação com variáveis bioquímicas e fatores de diálise como KT/V e URR.…”
Section: Discussionunclassified
“…In the malnourished and nourished patients according to BMI, SGA and NRS 2002, regardless of confounding factors (age and gender), only BMI was associated with HGS, that is, the mean HGS of the malnourished individuals according to BMI were significantly lower than those of the nourished individuals, which is in agreement with Norman et al 9 and Schlüssel et al 11 . Meanwhile, a study done with hemodialysis patients found that the mean BMI of patients above and within the tenth percentile for HGS did not differ 4 .…”
Section: Discussionmentioning
confidence: 97%
“…However, in the absence of a gold standard, scientists tried to identify new methods capable of accurately diagnosing malnutrition [2][3][4] . Many tools have been used; however, their validity is still controversial 5 .…”
Section: Introductionmentioning
confidence: 99%